A QUANTITATIVE ANALYSIS OF FACTORS INFLUENCING STUDENT MOTIVATION IN PRIVATE SCHOOLS IN SHARJAH, UAE: TEACHERS’ PERSPECTIVES (Proceedings of the International Conference on Education, 2025)
This study investigates the primary factors influencing student motivation in private schools in Sharjah, UAE. Addressing the challenge of maintaining student engagement, the research aims to identify strategies to enhance motivation and improve academic outcomes. A quantitative research method was employed, utilizing a survey distributed among teachers to collect data on effective motivational practices. The findings indicate that strategies such as fostering strong teacher-student relationships, using relevant examples, offering specific and consistent praise, allowing student autonomy, incorporating technology, and implementing token or point systems significantly contribute to enhancing motivation. Internal factors influencing motivation include the learning environment, teacher behavior and responsibility, classroom layout, curriculum design, teaching methodologies, assessment practices, and peer relationships. External factors identified include family circumstances, student interest in learning, self-regulation, and intrinsic motivation driven by the aspiration for higher academic performance. The study concludes that applying targeted strategies while addressing internal and external factors can create a supportive learning environment that fosters greater student engagement. These findings offer valuable insights for educators and policymakers to develop interventions that enhance classroom participation, ultimately improving student performance and outcomes.
Keywords: student motivation; learning environment; teaching strategies; internal and external factors